Biomarkers of Cervical Inflammation and Immunity Associated with Cervical Shedding of HIV-1 - Mauck, Christine (AIDS Res Hum Retroviruses, 2016)
Background: Cervicovaginal HIV shedding is associated with increased female-to-male and mother-to-child transmission. Genital inflammation may increase shedding through cytokines/chemokines which recruit and activate HIV target cells. We evaluated whether cervical immune mediators present before seroconversion affected HIV shedding and whether mediators differed between shedders and nonshedders. Methods: We used cervical samples from 187 African women with documented HIV seroconversion in the Hormonal Contraception and HIV study. Samples were from the two visits before seroconversion (T-2 and/or T-1), and/or at seroconversion (T0), and/or the two visits (T + 1 and/or T + 2) after seroconversion. We measured interleukin (IL)-1β, IL-1 Receptor Antagonist (IL-1RA), IL-6, IL-8, RANTES (Regulated on Activation, Normal T-Cell Expressed and Secreted), MIP-3α, vascular endothelial growth factor (VEGF), Intercellular Adhesion Molecule-1 (ICAM-1), secretory leukocyte protease inhibitor (SLPI), and BD-2 and used the Wilcoxon test and generalized linear models to evaluate the association between mediators and shedding. Results: The only immune mediator that differed at T-1 was RANTES, which was higher among shedders (p ≤ .05). HIV seroconversion was followed by significant decreases in many mediators, but a significant increase in RANTES. The magnitude of the change was significantly different for shedders versus nonshedders with regard to RANTES (increased in both groups, significantly more so in shedders), SLPI (decreased in both groups, significantly more so in shedders), and MIP-3α (decreased in shedders and increased in nonshedders). At T0, shedders had lower levels of SLPI and MIP-3α than nonshedders. Conclusions: In this study, a specific immune mediator profile was associated with risk of cervical HIV shedding. Higher and increasing levels of RANTES and lower and decreasing levels of SLPI and MIP-3α were associated with increased risk of HIV shedding.